2009
DOI: 10.1086/597078
|View full text |Cite
|
Sign up to set email alerts
|

What Is Next for Functional Requirements for Bibliographic Records? A Delphi Study

Abstract: This article reports on a Delphi study conducted to determine key issues and challenges facing Functional Requirements for Bibliographic Records (FRBR) research and practice. The Delphi panel consisted of thirty-three experts in the field who participated in a three-round issue-raising and consensus-building process via a Web-based survey instrument designed for this study. The panel members were asked to raise critical issues in each of five major areas based on themes in existing literature: (1) the FRBR mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 53 publications
0
15
0
1
Order By: Relevance
“…Others realize this as well. A Delphi study by Zhang and Salaba (2009) found that experts rank the need to verify that FRBR is appropriate with user studies very highly among the issues in the area of the FRBR model. There appear to be two possible ways to study users in connection with FRBR.…”
Section: Motivationmentioning
confidence: 99%
“…Others realize this as well. A Delphi study by Zhang and Salaba (2009) found that experts rank the need to verify that FRBR is appropriate with user studies very highly among the issues in the area of the FRBR model. There appear to be two possible ways to study users in connection with FRBR.…”
Section: Motivationmentioning
confidence: 99%
“…As there are also no true FRBR catalogs yet in existence, there is no real evidence that FRBR would truly enhance user experience in library catalogs. This was identified as an important issue in a Delphi study of leading FRBR research by Zhang and Salaba (2009b).…”
Section: Presentationsmentioning
confidence: 99%
“…Presentation description: FRBR user research and evaluation is essential to a better understanding of the FRBR model and development of systems that support user information seeking. However, FRBR‐related user research is the least addressed area in FRBR research and development [4]. Zhang and Salaba will report on various user studies that have been conducted in this area.…”
Section: Presentations and Panelistsmentioning
confidence: 99%